Evaluating the Implementation of Technology Design in Language learning - Siti Raudhah Maidari; Irmi Agustina; Budi Riyanto (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pelayaran Malahayati, 2022)
The promotion of language learning technology has widely used by many English teachers and learnersin improving the target language. This study aims to review the effectiveness of particular technology in language teaching and learning. Itconcerns on CALL (Computer Assisted Language Learning) that focus on Grammar checkers, Electronic dictionary, Chat, Blog and internet forum and discussion. The data is compiled through library research and classified into three categories towards the potential used of a certain technology on language learning. This study revealed that language learning by using technology leads to joyful learning where it improves students opportunities for interaction, obtains more feedback, have more time to construct the sentence and the most important is students access to the target language is increased.